Vector Density Analysis of Dengue Hemorrhagic Fever in Tumpok Teungoh Village, Lhokseumawe City - Sofia, Rizka; Juwita Sahputri (Open Access Indonesian Journal of Medical Reviews, 2022)
Dengue hemorrhagic fever (DHF) is an infectious disease of the dengue virus, which is transmitted by the Aedes aegypti mosquito as the main vector and Aedes albopictus as a potential vector. Monitoring the population density of Aedes aegypti is very important to assist in evaluating the presence of threats in each city, and so that mosquito eradication measures can be improved. The purpose of this study was to determine the density of the DHF vector in the village of Tumpok Teungoh, Lhokseumawe City. The population in this study were all houses in the village of Tumpok Teungoh, Lhokseumawe City, which amounted to 2,531 houses. The number of samples used is 100 houses which will be carried out by random sampling. Data was collected through direct observation by observing the type and number of containers as well as the presence of Aedes aegypti in water containers/holds in each house. Data analysis was carried out descriptively on the type of container, the number of larva-positive containers, the number of larva-positive houses, and the larval density, which was calculated based on the house index, container index, and Breteau index numbers. The results showed that the House Index (HI) was 29%, the container index (CI) was 20.5%, and the Breteau index (BI) was 41%. In conclusion, the density of DHF larvae in Tumpok Teungoh Village, Lhokseumawe City, is at level 5, which is the category of moderate risk of DHF transmission.